2013
DOI: 10.1097/iop.0b013e318279fdd6
|View full text |Cite
|
Sign up to set email alerts
|

Solitary Fibrous Tumor of the Orbit With Multiple Cavities

Abstract: Solitary fibrous tumors (SFTs) are rare spindle cell neoplasms of mesenchymal origin that most commonly arise within pleura and have also been reported in many extrapleural sites including the orbit. Cavitary changes within SFT of both pleura and extrapleural sites have been documented, but remain very rare. To the authors' knowledge, the third known case of an orbital solitary fibrous tumor containing large pseudocystic cavities is described. MRI demonstrated a heterogeneous enhancing mass with multiple cavit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 10 publications
1
8
0
Order By: Relevance
“…Painless, non-pulsating, incompressible masses can be touched by physical examination [24]. The patients involved in the current study had a mean age of 54 years old, and their clinical manifestations included exophthalmos, ptosis, abnormal eye position, and blurred vision, which were consistent with those reported previously [24][25][26][27].…”
Section: Clinical Manifestationssupporting
confidence: 82%
“…Painless, non-pulsating, incompressible masses can be touched by physical examination [24]. The patients involved in the current study had a mean age of 54 years old, and their clinical manifestations included exophthalmos, ptosis, abnormal eye position, and blurred vision, which were consistent with those reported previously [24][25][26][27].…”
Section: Clinical Manifestationssupporting
confidence: 82%
“…2 Although SFT was originally reported to be located within the pleura, 1 case studies from extrapleural sites of SFT have also been reported. [4][5][6][7][8][9] As SFT is an extremely rare tumor, its longterm clinical behavior is not known. This case may enlighten the mostly unknown clinical behavior of this tumor.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8][9] Rarely, it is found in the mediastinum, skin, meninges, orbit, upper respiratory tract, breast, thyroid, and peritoneum. 5 Solitary fibrous tumor exhibits a variable microscopic appearance, which necessitates immunohistochemistry to confirm the diagnosis.…”
mentioning
confidence: 99%
“…Although orbital SFTs are mostly solid tumours, partial or complete cystic changes have been reported in seven previous cases (three primary and four recurrent), but none of these occurred in the lacrimal gland. [3236]. Although the mere presence of cavitary lesions does not necessarily indicate aggressive behaviour, cystic degeneration poses a risk of recurrence and may suggest malignant transformation over time, especially in recurrent tumours.…”
Section: Discussionmentioning
confidence: 99%
“…[35]. The mechanism of cystic degeneration is unknown, but it has been suggested that the tumour outgrows its blood supply, leading to necrotic areas that are later reabsorbed, generating cystic spaces [32]. No data are available to establish whether there is a relationship between tumour age and the onset of cystic degeneration.…”
Section: Discussionmentioning
confidence: 99%